Fashion in the sustainabilit context (ModaPalavra e-periódico, 2013)
From the research "Ecomoda: dimensions of sustainability applied to the product's clothing", this article presents issues considered of value to the understanding of the concept of sustainability applied to the system to fashion and textile sector. The work was based on the ideas of Lee (2009), Fletcher and Grose (2011), Berlin (2012) who have developed concepts to define sustainability applied to fashion and clothing consumption. The research on the theories studied, analyzed and discussed in groups, involving the coordinator and research fellows and Outreach Program Ecomoda, served as the starting point for this article. The Outreach Program of the B.Sc. in Fashion UDESC was created in 2004 with the objective of disseminating the concept of environmental sustainability through the production and consumption conscious. Finally, presented examples of how professionals in the field of fashion are introducing sustainability concepts into products and services.
Keywords: fashion; sustainability; consumption